2022
DOI: 10.21203/rs.3.rs-2124092/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Durum Wheat Heat Tolerance Loci Defined via a North-South Gradient

Abstract: The global production of durum wheat (Triticum durumDesf.) is hindered by a constant rise in the frequency of severe heat stress. Three different germplasm panels were investigated under a range of heat stress to identify tolerant germplasm. The ‘discovery panel’ was field tested in the south of Morocco and along the Senegal River implementing a mild-to-strong North-South heat stress gradient. A subset of this same panel was also exposed to simulated terminal heat stress by applying plastic tunnels at the time… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Genetic analysis of heat tolerance in wheat is a hot topic in recent years, and many studies have been performed for heat stress tolerance at flowering and reproductive stages [65][66][67][68][69][70][71]. However, there is limited empirical studies focusing on HST at the seedling stage in wheat [1,36,72,73].…”
Section: Comparisons Of the Hst Qtls With Previously Reportedmentioning
confidence: 99%
“…Genetic analysis of heat tolerance in wheat is a hot topic in recent years, and many studies have been performed for heat stress tolerance at flowering and reproductive stages [65][66][67][68][69][70][71]. However, there is limited empirical studies focusing on HST at the seedling stage in wheat [1,36,72,73].…”
Section: Comparisons Of the Hst Qtls With Previously Reportedmentioning
confidence: 99%
“…Temperature-related variables that affected yield under HS were generally those calculated based on temperatures at grain fill (post anthesis), confirming what has been observed in several small-grains species, that some of the most important yield-limiting effects of heat on the present durum panel were related to high temperatures from flowering through grain filling stages, which affects several reproductive and/or physiological processes (Cossani and Reynolds, 2012;Fabian et al, 2019), or grain metabolic pathways (Wahid et al, 2007;Farooq et al, 2011;Gautam et al, 2014;Sharma et al, 2017). However, HS prior to anthesis and grain fill is also critically detrimental, affecting final yield consequent to a reduced source capacity and/or biomass available to support grain filling, particularly in its final stages (Xu et al, 2022;Barratt et al, 2024;Sall et al, 2024). In the current study, a substantial reduction was observed in biomass accumulated up to shortly after anthesis (NDVI), averaging 52%, second only to the effect on final GY.…”
Section: Discussionmentioning
confidence: 86%
“…The study of structural models, and in particular of GSEM, lays a foundation for the next steps in elucidating the physiological response to heat by mapping QTLs controlling the trait (Igolkina et al, 2020) and to implement either marker-assisted selection, if large effects QTLs are identified, or genomic prediction tailored to heat tolerance improvement of durum wheat . Most importantly, we believe that meaningful tools to link genetic knowledge and environmental specificity, such as those employed in the present study, can be part of the most needed translational research aimed at actually improving crop cultivars (Kole et al, 2015;Millet et al, 2019;Reynolds et al, 2021;Welcker et al, 2022;Della Coletta et al, 2023;Sall et al, 2024).…”
Section: Discussionmentioning
confidence: 98%